Asuhan Keperawatan Anak Pada An. H Dengan Pemberian Terapi Water Tepid Sponge Untuk Menurunkan Suhu Tubuh Pada Demam Tipoid Di Ruang Anak RSUD Pariaman Tahun 2023 - Rezki Yeti Yusra; Runanda Novianti Maulita (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Typhoid fever is a disease caused by the bacteria Salmonella Enterica Serovar Tyhpi (S Thypi), especially its derivative, Salmonella Thyphosa. Common symptoms that often occur in typhoid fever are fever with body temperature rising and falling, especially in the afternoon and evening. A non-pharmacological technique that can be used to reduce the increase in body temperature in fever patients is by water tepid sponge therapy. The aim of this study was to obtain an overview of nursing care for pediatric patients with typhoid fever after therapy water tepid sponge to lower body temperature. This research method used a case study design using a nursing care approach, namely assessment, nursing diagnosis, intervention, implementation and evaluation. Management of patients only uses interventions provided by administration water tepid sponge for 3 days for 20 minutes per day. The results of the study showed that the patient's body temperature decreased from 39.2°C to 36.8°C after nursing intervention. Intervention water tepid sponge can be used as a non-pharmacological alternative to reduce the body temperature of children suffering from hypertherm.